2021
DOI: 10.1101/2021.11.23.469725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fecal microbiota transplantation derived from Alzheimer’s disease mice worsens brain trauma outcomes in wild-type controls

Abstract: Traumatic brain injury (TBI) cause neuroinflammation, exaggerated immune response, and, consequently, neurodegeneration. The gut microbiome is an essential modulator of the immune system, impacting in the brain. There are not effective treatments for TBI, therefore, modulating the gut microbiome may shed novel therapeutics for the damaged brain. Also, in patients with Alzheimer’s disease (AD), the microbiota has been associated with a lack of diversity, which negatively modulates the immune system. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…In vivo studies conducted by Soriano et al in the C57BL/6 mouse model confirmed the roles of the intestinal microbiota in the pathogenesis of AD. Healthy mice treated with fecal microflora from mice with AD revealed larger areas of brain damage, increased numbers of activated microglia cells and reduced motor regeneration (Soriano et al, 2022). These studies provide the basis for the hypothesis that it is the microbiota that can improve Alzheimer's disease (AD) development; based on (Reitz, 2015;Moir et al, 2018;Megur et al, 2020;Pluta et al, 2020;Perkovic et al, 2021).…”
Section: Microbiotamentioning
confidence: 79%
“…In vivo studies conducted by Soriano et al in the C57BL/6 mouse model confirmed the roles of the intestinal microbiota in the pathogenesis of AD. Healthy mice treated with fecal microflora from mice with AD revealed larger areas of brain damage, increased numbers of activated microglia cells and reduced motor regeneration (Soriano et al, 2022). These studies provide the basis for the hypothesis that it is the microbiota that can improve Alzheimer's disease (AD) development; based on (Reitz, 2015;Moir et al, 2018;Megur et al, 2020;Pluta et al, 2020;Perkovic et al, 2021).…”
Section: Microbiotamentioning
confidence: 79%